Seed dispersal by terrestrial mammals in hurricane-impacted forests on the Atlantic coastal forests of Nicaragua after 2007 Hurricane Felix - Fung McLeod, Emily M. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2011